A new potassium-based intermediate and its role in the desorption properties of the K–Mg–N–H system. Issue 5 (14th January 2016) - Santoru, A.; Garroni, S.; Pistidda, C.; Milanese, C.; Girella, A.; Marini, A.; Masolo, E.; Valentoni, A.; Bergemann, N.; Le, T. T.; Cao, H.; Haase, D.; et al.
Abstract : In situ SR-PXD experiments revealed a new reaction mechanism of amide–hydride anionic exchange for the K–Mg–N–H system. Abstract : New insights into the reaction pathways of different potassium/magnesium amide–hydride based systems are discussed. In situ SR-PXD experiments were for the first time performed in order to reveal the evolution of the phases connected with the hydrogen releasing processes. Evidence of a new K–N–H intermediate is shown and discussed with particular focus on structural modification. Based on these results, a new reaction mechanism of amide–hydride anionic exchange is proposed.